2020
DOI: 10.1002/lno.11432
|View full text |Cite
|
Sign up to set email alerts
|

Role of delta‐front erosion in sustaining salt marshes under sea‐level rise and fluvial sediment decline

Abstract: Accelerating sea-level rise and decreasing riverine sediment supply are widely considered to lead to global losses of deltaic marshes and their valuable ecosystem services. However, little is known about the degree to which the related erosion of the seaward delta front can provide sediments to sustain salt marshes. Here, we present data from the mesomacrotidal Yangtze Delta demonstrating that marshes have continued to accrete vertically and laterally, despite rapid relative sea-level rise ($10 mm yr −1) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 103 publications
(163 reference statements)
2
55
0
Order By: Relevance
“…The study area has natural coastal wetlands with fertile soil (formed by the huge amount of sediment carried by the runoff of the Yangtze River and deposited at the interface of the river and the sea), which is a potentially an important land resource. Chongming Dongtan Wetland is a national nature reserve for birds and an internationally important Ramsar wetland [18]. Jiuduansha Wetland is also a national nature reserve [18].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The study area has natural coastal wetlands with fertile soil (formed by the huge amount of sediment carried by the runoff of the Yangtze River and deposited at the interface of the river and the sea), which is a potentially an important land resource. Chongming Dongtan Wetland is a national nature reserve for birds and an internationally important Ramsar wetland [18]. Jiuduansha Wetland is also a national nature reserve [18].…”
Section: Study Areamentioning
confidence: 99%
“…Chongming Dongtan Wetland is a national nature reserve for birds and an internationally important Ramsar wetland [18]. Jiuduansha Wetland is also a national nature reserve [18]. As a megacity in China, Shanghai has high carbon dioxide emissions from human activities.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of semantic effort also helps connect distant themes, such as those represented by the topical groups ecosystem-change-service and sedimentimpact-marsh (see the red and light-blue nodes in Figure 2). It does so, for example, by intensifying the "study of the state of salt marshes as impacted by changes in sediment fluxes from rivers, " a rare but cross-cutting topic (Rutherford et al, 2018;Yang et al, 2020).…”
Section: Sorting For Biologically Driven Synergies and Trade-offsmentioning
confidence: 99%
“…In a mesotidal system in Southeastern Essex, England, it was observed that fine-grain sediments eroded from the marsh edge are responsible for marsh accretion on the platform in response to SLR (Reed, 1988). Sediment coarsening at the delta front was observed in the Yangtze Delta, China, where erosion provided sediments to sustain salt marshes despite increasing sea levels and reduced riverine sediment loads in the last half century (Yang et al, 2018(Yang et al, , 2020.…”
Section: 1029/2020gl087862mentioning
confidence: 99%